2020
DOI: 10.21608/ejabf.2020.115070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of rotavirus Group A VP6 gene in Egyptian surface water, wastewater and diarrheal specimens

Abstract: Impact of rotavirus vaccine introduction and genotypic characteristics of rotavirus strains in children less than 5 years of age with gastroenteritis in Ethiopia: 2011-2016. Vaccine, 36: 7043-7047. American Public Health Association (APHA). (1998). Standard methods. 20 th Edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Our dataset indicated a high similarity to those of human RVA strains and particularly human Wa-like strains in the USA. These findings were in accordance with another studies in Egypt that reported the similarity between the VP6 and VP4 genes of RVA isolated from clinical and environmental samples and the Wa reference strain in the USA [ 12 , 40 ]. The low variations in VP6 sequences contained in the Egyptian G1P8 genotype may suggest that VP6 recombinant subunit vaccines would be useful candidates for rotavirus vaccination among Egyptian children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our dataset indicated a high similarity to those of human RVA strains and particularly human Wa-like strains in the USA. These findings were in accordance with another studies in Egypt that reported the similarity between the VP6 and VP4 genes of RVA isolated from clinical and environmental samples and the Wa reference strain in the USA [ 12 , 40 ]. The low variations in VP6 sequences contained in the Egyptian G1P8 genotype may suggest that VP6 recombinant subunit vaccines would be useful candidates for rotavirus vaccination among Egyptian children.…”
Section: Discussionsupporting
confidence: 93%
“…The current study is one of a handful of research projects on rotavirus disease in children under the age of five that has been conducted in Egypt [ 12 , 21 , 38 , 39 , 40 ]. This study reports the distribution of rotavirus isolated from fecal samples in a repeated cross-sectional study of 230 Egyptian children, ranging in age from birth to five years, between 2018 and 2020 in two major university hospitals in Egypt.…”
Section: Discussionmentioning
confidence: 99%